Humoral responses to SARS-CoV-2 vaccination in rituximab-treated patients depend on peripheral B cell re-population rather than the timings of the dosing - Rashwith Umesh; Aby Paul; Veena Shenoy; Sakir Ahmed; Somy Cherian; Arya Prasad; Padmanabha Shenoy (Indian Journal of Rheumatology)
Introduction: Previous exposure to Rituximab affects the immunogenicity of vaccination including that against coronavirus disease (COVID-19). However, dynamics of the effect of rituximab on vaccination are not well understood. This study aims to assess the role of timing of vaccine dosing and B-cell repopulation on vaccine seroconversion. Methods: Autoimmune rheumatic disease (AIRD) patients treated with rituximab who had completed two doses of COVID-19 vaccination were enrolled. Peripheral B-cell counts were estimated along with the titer of immunoglobulin G antibody-directed against the receptor-binding domain of spike1 protein of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Antibody titers of participants were compared against B-cell re-population. Results: Out of the 33 participants with available prevaccination B-cell counts, 11 did not have any detectable peripheral B cells before vaccination, and out of these patients, only 1 developed antibodies postvaccination, whereas, of the remaining 22, 18 (81.8%) had a positive seroconversion. Although all patients who had received the last dose of Rituximab at least 1 year before vaccination had antibodies, there was no direct correlation between time from the last dose and antibody positivity. B-cell re-population was strongly associated with seroconversion (P = 0.0001). Conclusion: In rituximab-treated patients, humoral responses to SARS-CoV-2 vaccination depend on peripheral B-cell re-population rather than the timing of the vaccination postrituximab infusion.